Scientific Substantiation of Thermal Leveling for Deformations in the Car Structure - Fomin, Oleksiy; Logvinenko, Oleksandr; Burlutsky, Oleksiy; Rybin, Andriy (International Journal of Engineering and Technology, 2018)
Railway transport is the foundation of the transport complex and part of the transport network of logistics chains. However, significant deterioration of rolling stock units (especially freight cars accounting for the greater part of all transportation) is an urgent problem of the rail industry. Therefore, the problems of renovation of the existing freight car fleet by developing and introducing domestic models which can effectively compete in terms of the technical and economic and operational indexes are of crucial importance. But the car structure suffers from various deformations at all service stages (production, maintenance and operation). The main type of these deformations is residual ones developing during the welding procedure, due to the thermal effect. Therefore, the issues concerning elimination of these deformations in production and maintenance are becoming ever more urgent. In particular, the most recognized and economy-oriented approach in the field is the one based on the thermal leveling of welded structures. The implementation of this approach requires some research aimed at scientific substantiation of the thermal leveling, as well as, specification of forms and heating temperatures, determination of heating form sizes, thermal leveling simulation and experimental verification of the results, optical microscopy and determination of mechanical characteristics.Â Â
Keywords: Experimental Research; Open-Top Car; Optimization Research; Railway Transport; Thermal Leveling.